Novel viruses: Update on the significance of papillomavirus infections in cats. Issue 5 (May 2019) - Munday, John S; Sharp, Claire R; Beatty, Julia A
Practical relevance: Prior to 1990 papillomaviruses (PVs) were not recognised to infect or cause disease in domestic cats. Since this time, the use of histology, immunohistochemistry and, more recently, molecular techniques has revealed that PVs almost certainly cause feline viral plaques and Bowenoid in situ carcinomas, oral papillomas and feline sarcoids. In addition, there is increasing evidence that PVs play a significant role in the development of feline cutaneous squamous cell carcinomas, one of the most common skin cancers of cats. Recent studies have also revealed that most cats are asymptomatically infected with PVs. This raises a critical question that is currently unanswered: why do only a small proportion of infected cats develop disease? In the future it may be possible to prevent PV-induced diseases by using a vaccine to prevent PV infection. Alternatively, novel therapies may be developed that prevent PVs from causing clinical disease by stimulating the host immune response. Clinical challenges: A recognition of the skin diseases caused by PVs is important to more accurately predict disease progression. Unfortunately, there are currently no non-surgical treatments that have been proven to be beneficial in cats and clinical management of PV-induced skin disease in cats can be challenging. Global importance: PVs have a worldwide distribution and negatively impact feline health and welfare globally. Audience: This review is aimed at clinicians, especially those who regularly treat cats with skin disease. The review will also be useful to oncologists and researchers who have an interest in how cancer develops in cats. Evidence base: In producing this update the authors have drawn on recently published peer-reviewed literature.